Formulation and laboratory efficacy of isaria fumosorosea against bagworms (Metisa plana walker and Pteroma pendula joannis) (lepidoptera: psychidae) - Syarif, Muhammad Nurul Yaqin (2017)
Relying solely on chemical insecticides for bagworm control in oil palm plantation could lead to many consequences to the ecosystem, environment and human. Thus, developing mycoinsecticide that able to control this pest could be the alternative to reduce chemical insecticides dependence. Entomopathogenic fungi might fulfil their potential with suitable choice of formulation and stable throughout the application and storage period either in biological, chemical, or physical aspect. Wettable powder is the formulation to be developed due to its easy and cheap production procedure. In this study, three fungi isolated from the infected Pteroma pendula collected from United Malacca Berhad (UMB) plantations in Pahang and Negeri Sembilan were found to be Isaria fumosorosea based on the morphological observations. Those three isolates were identified using molecular identification procedure along with six isolates obtained from Forest Entomology Laboratory, Faculty of Forestry Universiti Putra Malaysia (UPM). Six of the isolates were I.fumosorosea where isolate BSB01 isolated of infected bagworms from UMB Plantation in Kemayan, Pahang was the most virulent isolates against P.pendula. This isolate was then mass produced and formulated with surfactants and filler. The compatibility of dispersants and wetting agents with this isolate was determined earlier before being used in wettable powder formulation. Screening the surfactants against I.fumosorosea BSB01 conidia viability and fungal growth were conducted on the isolate, aerial conidia and submerged propagules. Surfactants found to be qualified were TERSPERSE® 2105, TERSPERSE® 2700, ELTESOL® SC, ELTESOL® SX, sodium naphthalenesulfonate, sodium lignosulfonate, sodium polyacrylates, and SIPERNAT® 22S. Among those qualified surfactants, two of them are wetting agents (ELTESOL® SC and ELTESOL® SX). Concentration of surfactant affects the conidia viability at 10% or higher. A surfactant system consisted of two dispersants and a wetting agent were prepared using pseudoternary phase diagram. Stable regions in each surfactant system were combined to find the mutual stable region. The single point was selected from the mutual stable region with the limit of wetting agents fixed at 15%. The stable region showed satisfying physical stability against kaolin. The best point was found to be at the ratio of 52:33:15 (Dispersant 1:Dispersant 2:Wetting agents). The surfactant ratio was then characterised with the presence of fungal aerial conidia and fungal submerged propagules. Submerged fungal propagules formulations showed better physical stability compared to the aerial conidia formulation. Although all formulations showed a steep decline of active colony counting from 9.0 × 108 to 1.0 × 108 cfu mL-1 within the first three days storage, these formulations maintained this viability until 90 days. Biological efficacy of the formulated submerged propagules were determined where all formulations showed no significant difference of LT50 values when compared with unformulated against Metisa plana and P.pendula.